Islamic Theological Reflections on Humanitarian Principles Towards Queer: Perspective of Qur’anic Interpretation - Sa'dan, Masthuriyah; M. Mukhtasar Syamsuddin; Agus Himmawan Utomo (The Faculty of Ushuluddin and Humanities, Universitas Islam Negeri Walisongo Semarang, Indonesia, 2024)
This research examines the principles of queer humanity in religious teachings written in the Qur'an. This research uses a qualitative literature study method, while the Qur'anic text reading uses Nasr Hamid Abu Zayd's contextual reading method. This study found several findings: First, humans are bound in a primordial covenant with God, and human life's orientation is to recognize God's Oneness. Second, humans are born in a state of fitrah (pure). Third, humans are ethical and moral beings. Fourth, every human person is valuable. Because the principle of humanity is written in the Qur'an, it is appropriate for humanity to have a religious, ethical attitude toward queer people by promoting the principles of justice, tolerance, and equality between human beings. This religious, ethical attitude is a guideline for human life regardless of differences in gender identity and sexual orientation. The principles of humanity in the teachings of Islam written in the Qur'an and hadith place humans, both men, women, and queers, as equal beings before God.